Unveiling challenges of aluminium electrode fouling and passivation in electrocoagulation treatment system for sustainable water management of coastal Borneo peatlands : A focused review - Nazeri, Abdul Rahman; Calvin, Jose Jol; Allene, Albania Linus; Siti Noor Linda, Taib; Arif, Parabi; Chieng, Kwong Ming; Astisza Syahla Ludmilla, Parabi; Anthonette, James; Nur Syazwa, Samsol; Sebastian Belun, John; Airul Azhar, Jitai; Dayang Fadhilatul Aisyah, Abang Abdul Hamid (Elsevier Inc., 2025)
The treatment of brackish peat water presents a formidable challenge due to its elevated levels of natural organic matter and salinity which not only hinder conventional water treatment systems but also necessitate an innovative approach to effectively manage these complex water characteristics. In response to these challenges, electrocoagulation has emerged as a promising alternative by utilizing electrochemical processes to efficiently destabilize and eliminate contaminants in brackish peat water sources. As such, this review aims to unveil challenges of aluminium electrodes fouling and passivation in electrocoagulation treatment system for sustainable water management of coastal Borneo peatlands. Several studies in the literature highlight that key operating parameters, especially electric current and voltage which play a pivotal role in influencing the overall effectiveness of these electrocoagulation systems. Although aluminium electrodes demonstrate high contaminants removal efficiencies, it remains susceptible to fouling and passivation due to contaminant buildup and oxide layer formation which increase electrical resistance and decrease electroactivity of redox reactions. The novelty of this review lies in its focused synthesis of fouling and passivation dynamics through the integration of Tafel plot analyses and advanced characterization techniques, particularly Energy Dispersive X-Ray (EDX) spectroscopy. Furthermore, a thorough understanding of the adsorption mechanisms, particularly through the interaction between aluminium hydroxides and contaminants is essential for enhancing system efficiency and mitigating fouling. Additionally, optimizing the electrocoagulation treatment system and conducting a detailed analysis of adsorption mechanisms, particularly through Tafel plot analysis are pivotal for enhancing the system efficiency. Advanced analytical methods such as Energy Dispersive X-Ray (EDX) spectroscopy provide deeper insights into floc composition that essential for improving contaminants removal strategies. Overall, this review offers a focused assessment on the interplay between brackish peat water and electrocoagulation in order to provide a foundation for future research aimed at developing sustainable treatment systems for coastal Borneo peatlands. 1.